2011
DOI: 10.1128/aac.00311-11
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Moxidectin into Breast Milk and Pharmacokinetics in Healthy Lactating Women

Abstract: Moxidectin is a macrocyclic lactone drug derived from the actinomycete Streptomyces cyanogriseus and is currently being used as a veterinary product for the prevention of canine heartworm disease and for the treatment of internal and external parasites in cattle, sheep, goats, and horses. It is being developed by the World Health Organization (WHO) as a potential macrofilaricidal agent for mass drug administration for the elimination of onchocerciasis (river blindness) in humans caused by the parasitic worm On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 10 publications
1
39
0
Order By: Relevance
“…7,15 Administration of single oral midazolam doses 7 and 89 days after moxidectin administration does not appear to affect moxidectin PK parameters. Current treatment of onchocerciasis involves single doses of ivermectin administered annually by community health workers throughout infected areas.…”
Section: Discussionmentioning
confidence: 99%
“…7,15 Administration of single oral midazolam doses 7 and 89 days after moxidectin administration does not appear to affect moxidectin PK parameters. Current treatment of onchocerciasis involves single doses of ivermectin administered annually by community health workers throughout infected areas.…”
Section: Discussionmentioning
confidence: 99%
“…No identifiable pro-arrhythmic risk was identified through routine electrocardiogram (ECG) safety assessment of 1,105 patients with onchocerciasis and 244 healthy volunteers who received single oral doses of moxidectin up to 36 mg in phase I to III clinical trials. 6,7,[9][10][11][12][13] Onchocerciasis is endemic in the most remote and resource-poor settings of sub-Saharan Africa and treatment with ivermectin is currently through mass drug administration programs involving whole communities (excluding young children and pregnant women) with limited medical supervision or follow-up. Moxidectin is likely to have a similar usage, providing a rationale for conducting a definitive human QT prolongation risk-assessment to confirm earlier findings.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
“…An in vivo cardiovascular safety pharmacology study showed no adverse effects (AEs) of moxidectin on the cardiovascular system in the dog at up to 1 mg/kg 6 . No identifiable pro‐arrhythmic risk was identified through routine electrocardiogram (ECG) safety assessment of 1,105 patients with onchocerciasis and 244 healthy volunteers who received single oral doses of moxidectin up to 36 mg in phase I to III clinical trials …”
mentioning
confidence: 99%
“…Research into moxidectin’s potential to have a higher effect on O. volvulus viability and/or fertility than ivermectin was initiated by WHO/TDR in the late 1990’s (Tagboto and Townson, 1996). Five Phase 1 studies in healthy volunteers were conducted (Cotreau et al., 2003, Korth-Bradley et al., 2011, Korth-Bradley et al., 2012, Korth-Bradley et al., 2013, Korth-Bradley et al., 2014). A Phase 2 study in Ghana determined whether moxidectin was safe enough in O. volvulus infected people to be evaluated in a Phase 3 study and obtained initial efficacy data (Awadzi et al., 2014).…”
Section: Research For New Drugs For Onchocerciasis Control and Eliminmentioning
confidence: 99%